Development of a Business Framework for the Enhancement of the Business Performance of Selected Small-Scale Businesses - Maria Gisela H. Calambas (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research study developed a business framework or model for the enhancement of the business performance of small-scale businesses in Ragay, Camarines Sur which were assisted through micro- financing specifically the following were looked into first, the description of small-scale businesses in terms of line of business, capitalization and micro- financing availment. Second, the impact of microfinancing on these businesses along the aspects of liquidity, inventory turnover and return on investments. Both qualitative and quantitative technique were used in the study. In using qualitative method an interview guide was utilized and a focused group discussion was conducted among the 10 respondents and survey questionnaire for quantitative approach in determining the acceptance of the model. After careful analysis of the study, it was revealed that 10 of the respondents said that the source of their capital to put up the business was from MFIs and 1 had said from personal saving. Majority of the respondents about 60 percent had availed from Card Bank Incorporated. 40 percent had availed from ARDCI. 4 of the respondents had availed the amount of 30 000-40 000php with the term of 9 months and with 12 percent interest rate. With regards to the impact of Microfinancing it showed that in terms of liquidity the sari-sari store, meat shop and buy and sell of rice and palay were moderately liquid while majority of the rest were not much liquid. In inventory turnover, the demand lead time and the number of days replenish showed a very highly efficient among sari- sari store, meat shop and fishmonger while the buy and sell of nipa had a very low efficiency. Majority of the respondents had a very low efficient return on investment. It can be concluded from the study that respondents were highly benefited by MFIS in giving leeway to them with regards to their starting capital however they didn’t realize the burden of high interest being charged causing them a hard time paying their weekly dues which led to difficulties in operating their business in its day-to-day operation.